PELATIHAN GOOGLE BUSINESS PROFILE DALAM MENDUKUNG TRANSFORMASI DIGITAL UMKM WISATA - Tituk Utari; Aprilina Dwi Astuti; Ardian Setio Utomo; Sarwanto Sarwanto (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
Digital transformation has become a strategic necessity for tourism micro, small, and medium enterprises (MSMEs) to increase visibility, competitiveness, and market access in the digital economy era. However, in practice, many tourism MSMEs have not been able to optimize their business's digital identity, particularly through the use of Google Business Profile (GBP) as a location-based promotional medium. This Community Service activity aims to improve the digital literacy and skills of tourism MSMEs under the auspices of the Temanggung Regency Culture and Tourism Office, Central Java, through training on creating and managing Google Business Profiles. The activity implementation method includes material delivery, direct practice, and assistance in account creation and business profile optimization. The results of the activity showed an increase in participants' understanding of the importance of a business's digital presence, their ability to create and manage Google Business Profiles independently, and their readiness to utilize digital platforms as a means of sustainable promotion. The results of the activity demonstrated an increased understanding among participants regarding the importance of a digital business presence, their ability to independently create and manage Google Business Profiles, and their readiness to utilize digital platforms as a sustainable promotional tool. This activity provided added value in the form of an easily replicable, applicable training model relevant to the needs of locally-based tourism MSMEs. Thus, the Google Business Profile training contributed to supporting the digital transformation of tourism MSMEs and strengthening the information technology-based regional tourism ecosystem. ABSTRAK Transformasi digital menjadi kebutuhan strategis bagi usaha mikro, kecil, dan menengah (UMKM) wisata dalam meningkatkan visibilitas, daya saing, dan akses pasar di era ekonomi digital. Namun, pada praktiknya masih banyak pelaku UMKM wisata yang belum mampu mengoptimalkan identitas digital usahanya, khususnya melalui pemanfaatan Google Business Profile (GBP) sebagai media promosi berbasis lokasi. Kegiatan Pengabdian kepada Masyarakat ini bertujuan untuk meningkatkan literasi dan keterampilan digital pelaku UMKM wisata di bawah naungan Dinas Kebudayaan dan Pariwisata Kabupaten Temanggung, Jawa Tengah, melalui pelatihan pembuatan dan pengelolaan Google Business Profile. Metode pelaksanaan kegiatan meliputi penyampaian materi, praktik langsung, serta pendampingan pembuatan akun dan optimalisasi profil usaha. Hasil kegiatan menunjukkan adanya peningkatan pemahaman peserta mengenai pentingnya kehadiran digital usaha, kemampuan dalam membuat serta mengelola Google Business Profile secara mandiri, serta kesiapan UMKM wisata untuk memanfaatkan platform digital sebagai sarana promosi yang berkelanjutan. Kegiatan ini memberikan nilai tambah berupa model pelatihan aplikatif yang mudah direplikasi dan relevan dengan kebutuhan UMKM wisata berbasis lokal. Dengan demikian, pelatihan Google Business Profile berkontribusi dalam mendukung transformasi digital UMKM wisata serta memperkuat ekosistem pariwisata daerah berbasis teknologi informasi.